Trojan Horse Delivery Strategies of Natural Medicine Monomers: Challenges and Limitations in Improving Brain Targeting - Kelu Lei; Lanyu Zhou; Min Dan; Fei Yang; Tiantian Jian; Juan Xin; Zhigang Yu; Yue Wang (Pharmaceutics)
Central nervous system (CNS) diseases, such as brain tumors, Alzheimer’s disease, and Parkinson’s disease, significantly impact patients’ quality of life and impose substantial economic burdens on society. The blood–brain barrier (BBB) limits the effective delivery of most therapeutic drugs, especially natural products, despite their potential therapeutic effects. The Trojan Horse strategy, using nanotechnology to disguise drugs as “cargo”, enables them to bypass the BBB, enhancing targeting and therapeutic efficacy. This review explores the applications of natural products in the treatment of CNS diseases, discusses the challenges posed by the BBB, and analyzes the advantages and limitations of the Trojan Horse strategy. Despite the existing technical challenges, future research is expected to enhance the application of natural drugs in CNS treatment by integrating nanotechnology, improving delivery mechanisms, and optimizing targeting characteristics.